An Analysis of Translating Figurative Expressions from Arabic into English Using Newmark’s Theory - Al_mafrachi , Assist.Lec. Tiba faris kadhim (Manar Elsharq Journal for Literature and Language Studies, 2026)
This study explores the challenges of translating figurative language, particularly metaphors and similes, from English into Arabic. It examines how cultural differences and the lack of direct equivalents affect translation and evaluates the effectiveness of semantic and communicative approaches. Findings show that figurative expressions pose significant difficulties due to their cultural specificity and implicit meanings, often leading to misinterpretation if translators lack cultural awareness. Semantic translation preserves the original meaning and style, while communicative translation ensures clarity and naturalness for the target audience. The research concludes that effective translation requires a balanced use of both approaches, tailored to the text and context. These insights provide practical guidance for translators and students in overcoming linguistic and cultural challenges in figurative language translation.